Determination of left atrial volume in healthy dogs and dogs with myxomatous mitral valve disease - Franco, Rodrigo P. (2016)
The left atrial volume (LAV) can be obtained using the biplane Simpson's method via echocardiography. Although in medicine this parameter has been considered to be a prognostic marker of left atrial enlargement in several cardiac diseases, in dogs with myxomatous mitral valve degeneration (MMVD), a valvulopathy characterized by left atrial (LA) volume overload, atrial enlargement is usually assessed by the LA-to-Aorta ratio (LA:Ao). Therefore, the body surface area (BSA)-indexed LAV was measured in healthy dogs and in dogs with MMVD using the biplane Simpson's method. For this purpose, a total of 107 healthy dogs (control) and 81 dogs with MMVD in ACVIM stages B1, B2 and C were assessed, with LAV being calculated during atrial diastole (d) and systole (s) through the biplane Simpson's method. Two-dimensional apical four-chamber (4C) and two-chamber (2C) images were obtained in every dog through the left parasternal window. The values obtained from healthy dogs were correlated with body weight using Pearson's test. An analysis of variance (ANOVA) and Tukey's test were used to compare healthy and MMVD dogs, as well as to investigate differences according with MMVD stages. A strong positive correlation was documented between either LAVd (r > 0.77) or LAVs (r > 0.73) and body weight in healthy dogs. The BSA-indexed LAV calculated for MMVD dogs was significantly different (p < 0.01) from that obtained for the control group. Also, LAV was significantly different (P < 0.05) when stages B2 and C, and B1 and C were compared. In conclusion, this study provided a reference for left atrial volume and the applicability of this technique to assess atrial overload in dogs with varying-stage MMVD.